2020
DOI: 10.1039/d0sc04401f
|View full text |Cite
|
Sign up to set email alerts
|

Glycoside hydrolase stabilization of transition state charge: new directions for inhibitor design

Abstract: Positive charge stabilized on remote C5-allylic center with catalysis occurring via a loose SN2 transition state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…One crucial point is how the positive charge of glycosyl cations is stabilized by these enzymes, which often rely on intermolecular polar contacts, forming ion-pairs, typically involving carboxylate side chains or even phosphate modifications . It has also been shown that GHs may stabilize transition states even from remote positions to the anomeric center …”
Section: Interactions Of Glycosyl Cations: From Enzymes To Model Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…One crucial point is how the positive charge of glycosyl cations is stabilized by these enzymes, which often rely on intermolecular polar contacts, forming ion-pairs, typically involving carboxylate side chains or even phosphate modifications . It has also been shown that GHs may stabilize transition states even from remote positions to the anomeric center …”
Section: Interactions Of Glycosyl Cations: From Enzymes To Model Systemsmentioning
confidence: 99%
“…73 It has also been shown that GHs may stabilize transition states even from remote positions to the anomeric center. 74 The Influence of Aromatic Interactions on the Stability of Glycosyl Cations. From Enzymes to Model Systems As described above, chemical modifications of the glycosyl donors that facilitate the development of positive charge at the anomeric center provide enhanced reactivities.…”
Section: Enzymes To Model Systems Glycosyl Cations As Central Entitie...mentioning
confidence: 99%
“…[12] One of the strategies to inhibit a GH is based on designing TS mimics whose conformation is similar to the oxocarbenium ion-like ring. [13][14][15][16] In parallel, developing chemical derivatives of the natural substrate of GHs has emerged as a procedure to inhibit glycosidases. The most common technique utilizes sulfuration of the glycosidic bond (S-glycoside).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the carbasugar covalent inhibitors, acetals require less catalytic assistance to traverse cationic TSs for the formation and hydrolysis of glycosylated GH intermediates. This marked difference in enzyme efficiency toward the natural substrates versus our carbasugar covalent inhibitors gives the carbasugar class of compounds high potential as Chemical Biology tools. , …”
Section: Results and Discussionmentioning
confidence: 99%